BOLD fMRI activation induced by vagus nerve stimulation in seizure patients. Issue 6 (1st June 2003) - Liu, W-C; Mosier, K; Kalnin, A J; Marks, D
Abstract : Objective: To identify the cerebral activated regions associated with the vagus nerve stimulation in epilepsy patients. Design: Blood oxygenation level dependent functional magnetic resonance imaging (BOLD fMRI) was employed to detect areas of the brain activated by vagus nerve stimulation in five patients with documented complex partial seizures. Methods: Functional MRI was done on a GE 1.5T Echospeed horizon scanner. Before each patient entered the scanner, the vagal nerve stimulator was set to a specific ON–OFF paradigm so that the data could be analysed using a box-car type of design. The brains were scanned both anatomically and functionally. The functional images were corrected for head motion and co-registered to the anatomical images. Maps of the activated areas were generated and analysed using the brain mapping software, SPM99. The threshold for activation was chosen as p < 0.001. Results: All patients showed activation in the frontal and occipital lobes. However, activation in the thalamus was seen only in the two patients with improved seizure control. Conclusions: BOLD fMRI can detect activation associated with vagus nerve stimulation. There may be a relation between thalamic activation and a favourable clinical outcome.